2017
DOI: 10.1177/0950422217698524
|View full text |Cite
|
Sign up to set email alerts
|

Obstacles to innovation in Brazil

Abstract: Through an investigation of data available from the Brazilian Innovation Survey (Pesquisa de Inovação) of the Brazilian Institute of Geography and Statistics (Instituto Brasileiro de Geografia e Estatística) and from a national survey on university–firm interactions (the BR Survey), the authors show that Brazilian industrial firms lack qualified individuals for two key activities: the promotion of innovation and the establishment of a dialogue between universities and firms. Brazilian firms’ weaknesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…Theoretical analysis can help in setting the limits of discussions to the most frequent problems encountered in the partnerships. In this context, our bibliometric analysis established that some of the selected papers consider strategy models, namely: resource-based theory (n = 3; Alunurm et al 2020;Galán-Muros and Plewa 2016;Wirsich et al 2016); knowledge-based theory (n = 1; Santoro and Bierly 2006); evolutionary economics (n = 2; Rapini et al 2017;Simachev et al 2014); institutional theory (n = 2; Brundin et al 2008;Lind et al 2013); and agency theory (n = 2; Calvo et al 2019;Siegel et al 2003). Based on the findings of this systematic review, we conclude that future research should explore the points summarized in Table 7.…”
Section: Conclusion Limitations and Future Research Directionsmentioning
confidence: 98%
See 2 more Smart Citations
“…Theoretical analysis can help in setting the limits of discussions to the most frequent problems encountered in the partnerships. In this context, our bibliometric analysis established that some of the selected papers consider strategy models, namely: resource-based theory (n = 3; Alunurm et al 2020;Galán-Muros and Plewa 2016;Wirsich et al 2016); knowledge-based theory (n = 1; Santoro and Bierly 2006); evolutionary economics (n = 2; Rapini et al 2017;Simachev et al 2014); institutional theory (n = 2; Brundin et al 2008;Lind et al 2013); and agency theory (n = 2; Calvo et al 2019;Siegel et al 2003). Based on the findings of this systematic review, we conclude that future research should explore the points summarized in Table 7.…”
Section: Conclusion Limitations and Future Research Directionsmentioning
confidence: 98%
“…The strategic dimension concerns the difference between partners regarding the time standpoint, in that universities take a long-term view of research while industry has a short-term perception for research and implementation. Other authors have also identified this barrier (Alunurm et al 2020 ; Bruneel et al 2010 ; Galán-Muros and Plewa 2016 ; Ghauri and Rosendo-Rios 2016 ; Mannak et al 2019 ; Rapini et al 2017 ; Villani 2013 ) and recommend that the issue be taken into account at the planning stage of collaborative research. The tactical dimension relates to the need for participants from different organizations and cultures to meet together for collaborative activities, such as conceptualization and brainstorming, without any of the parties dominating.…”
Section: Content Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, this relationship, although increasing, is still limited and is often given as another key explanation for the country's low innovation results. Heavy bureaucracy and low incentives in universities (Reynolds and De Negri, 2019), as well as a lack of qualified personnel in firms (Rapini, Chiarini and Bittencourt, 2016) hinder such collaborations.…”
Section: Collaboration Between Enterprises and Academia Is Still Limitedmentioning
confidence: 99%
“…No Brasil, esse relacionamento, apesar de crescente, ainda é limitado, o que é frequentemente apresentado como outra explicação importante para os baixos resultados de inovação do país. A burocracia pesada e os baixos incentivos nas universidades (Reynolds e De Negri, 2019), bem como a falta de pessoal qualificado nas empresas (Rapini, Chiarini e Bittencourt, 2016), dificultam essas colaborações.…”
Section: A Colaboração Entre Empresas E Academia Ainda é Limitadaunclassified